Correlation between the mortality from cancer of the breast, prostate, lung, colon and pancreas and pro capite food consumption in Serbia, 1991-2010 - Ilic, Milena; Vasiljevic, Sladjana; Vlaisavljevic, Zeljko; Konevic, Slavica (European Journal of Oncology and Environmental Health, 2014)
Summary. Aim: The purpose of this study was to investigate the association between pro capite food consumption and mortality rates of the five commonest cancers in Serbia. Materials and methods: The correlation between the age-adjusted mortality rates of breast, prostate, lung, colon and pancreatic cancer and pro capite food consumption was calculated by Pearson’ correlation coefficient. Results: The coefficients of correlation indicate that pro capite consumption of animal fat (r=-0.67), beef (r=-0.80), milk (r=-0.47), wine (r=-0.72) and hard drinks (r=-0.81) were significantly negatively correlated with female breast cancer mortality rates, while consumption of poultry (r=0.61), dried and processed meat (r=0.57), fish (r=0.53), eggs (r=0.71), and yogurt (r=0.66) were positively correlated. A positive correlation was apparent in the four cancers (prostate, lung, colon and pancreatic cancer) mortality rates with pro capite consumption of vegetable oil, poultry, dried and processed meat, fish, eggs, yogurt and other dairy products, and coffee. Consumption of beer was correlated only with pancreatic cancer mortality rates (r=0.52). Conclusions: Striking changes in mortality rates of breast, prostate, lung, colon and pancreatic cancers have been shown, which may be at least in part attributable to the concurrent nutrition transition.